The Impact of Audio-Lingual Approaches on Vocabulary Acquisition: تأثير الطريقة السمعية الشفهية اللغوية على اكتساب المفردات - Widiyana, Ayu; Fahrurrazi (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2024)
The Audio-Lingual Method is a well-known approach in Arabic language instruction, aimed at enhancing language proficiency. This method focuses on teaching foreign languages by emphasizing listening and reading comprehension. Vocabulary (mufradat), which refers to the collection of words known to an individual or within a language, plays a crucial role in constructing sentences and enriching students' language skills. However, students often encounter challenges in understanding Arabic, both in conversations and texts, particularly when learning vocabulary. Mastering Arabic vocabulary is essential for comprehension; nevertheless, without adequate vocabulary acquisition, it becomes difficult for learners to express themselves effectively in oral and written forms. This study aims to evaluate the effectiveness of the Audio-Lingual Method among grade XI students at MAN Lhokseumawe. A quantitative research approach was employed, utilizing Quasi-Experimental design with nonequivalent control group techniques. The study population included students from classes XIa, XIb, and XIc, with class XIb serving as the control group and class XIc as the experimental group. Each group consisted of 24 students. The findings of the study confirmed the research hypothesis. Based on the Wilcoxon Signed-Ranks Test, the p-value was < 0.05 (0.00), indicating that the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. These results demonstrate the effectiveness of the Audio-Lingual Method in enhancing students' vocabulary acquisition. The findings imply that the Audio-Lingual Method effectively enhances students’ Arabic vocabulary and should be applied more widely in language instruction.